Innovation in Learning at Madrasah Ibtidaiyah: Integrating Islamic Values Amidst Tradition and Secular Modernity Debate - Srinio, Fuad; Sholihah, Maidatus; Sebgag, Saliha (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Madrasah Ibtidaiyah (Islamic Elementary School) faces the challenge of balancing preserving Islamic values with the demands of secular modernity in education. This gap creates a dilemma between educational goals focused on spirituality and morality and the need to meet the increasingly evolving global education standards. This study examines how Madrasah Ibtidaiyah (MI) integrates Islamic values into learning while remaining relevant to modern educational demands. The method used is qualitative, with case studies conducted at several Madrasah Ibtidaiyah in Indonesia. Data was collected through interviews with school principals, teachers, and students and direct observation of classroom activities. The findings show that madrasahs have successfully implemented learning innovations such as using technology, project-based approaches, and strengthening community involvement. These innovations allow the integration of Islamic values with secular subjects without compromising religious principles. This holistic learning focuses on character development, critical skills, and forming student identities that balance spiritual and intellectual aspects. The discussion of these findings reveals that the success lies in the madrasahs’ ability to adapt the curriculum to support students’ moral and intellectual development while preparing them to face modern world challenges. This study shows that madrasahs can produce a generation that is religiously deep and ready to compete in the global educational arena.